Efectividad del catéter central de inserción periférica en miembros inferiores en comparación con la inserción en miembros superiores para la disminución de complicaciones mecánicas e infección en neonatos en cuidados intensivos. - Catanaima Ramírez, Yumaris Valentina (2020)
Method: The Systematic Review design was used, the search was limited to articles with full text, subjected to a critical reading, using the Jover evaluation to identify its degree of evidence. Results: 10 articles corresponding to China 20%, Canada 30%, 10% Australia, Sweden 10% and USA 30% were selected comparatively. 40% of the studies stated that there were no significant differences in complications that require the elimination of the PICC, 40% expressed that the non-central position is a risk factor for complications and elimination, whose tendency increases in MS and 20% stated that the PICC placement in MI is associated with significantly higher risk of complications. Conclusions: Of the 10 articles systematically reviewed, 6/10 evidenced mechanical complications and infection according to the insertion site, adding that the central location of the PICC tip can have a significant impact on the complications. Only 4/10 articles found no difference in complications according to the insertion zone. Recommendations: Increased knowledge about the types of complications of the PICC according to the insertion site: MS or MI, can help focus prevention and location-based surveillance efforts, to improve safety and minimize complications of these in the patient in the NICU.